Peri-interventional endothelin-A receptor blockade improves long-term outcome in patients with ST-elevation acute myocardial infarction - Adlbrecht, Christopher; Wurm, Raphael; Humenberger, Michael; Andreas, Martin; Redwan, Bassam; Distelmaier, Klaus; Klappacher, Günter; Lang, Irene M. (Thrombosis and Haemostasis, 2014)
Endothelin (ET)-1 is a pro-fibrotic vasoconstrictive peptide causing microvascular dysfunction and cardiac remodelling after acute ST-elevation myocardial infarction (STEMI). It acts via two distinct receptors, ET-A and ET-B, and is involved in inflammation and atherogenesis. Patients with posterior-wall STEMI were randomly assigned to intravenous BQ-123 at 400 nmol/minute (min) or placebo over 60 min, starting immediately prior to primary percutaneous coronary intervention (n=54). Peripheral blood samples were drawn at baseline as well as after 24 hours and 30 days. Myeloperoxidase (MPO), as a marker of neutrophil activation and matrix metalloproteinase 9 (MMP-9), a marker of extracellular matrix degradation were measured in plasma. Clinical follow-up was conducted by an investigator blinded to treatment allocation over three years. During the median follow-up period of 3.6 years (interquartile range [IQR] 3.3–4.1) we observed a longer event-free survival in patients randomised to receive BQ-123 compared with patients randomised to placebo (mean 4.5 years (95% confidence interval: 3.9–5) versus mean 3 years (2.2–3.7), p=0.031). Patients randomised to ET-A receptor blockade demonstrated a greater reduction of MPO levels from baseline to 24 hours compared to placebo-treated patients (-177 ng/ml (IQR 103–274) vs –108 ng/ml (74–147), p=0.006). In addition, a pronounced drop in MMP-9 levels (-568 ng/ml (44–1157) vs –117 ng/ml (57–561), p=0.018) was observed. There was no significant difference in amino-terminal propetide of pro-collagen type III levels. In conclusion, short-term administration of BQ-123 leads to a reduction in MPO, as well as MMP-9 plasma levels and to a longer event-free survival in patients with STEMI.ClinicalTrials.gov Identifier: NCT00502528
Keywords: Acute myocardial infarction; endothelin; BQ-123; percutaneous coronary intervention; remodelling; clinical outcome